The Effectiveness of Positive Psychology Intervention in Turkey: A Meta-Analysis - Gürgan, Uğur; Ulubay, Gizem (Journal of History Culture and Art Research, 2020)
The aim of this study is to determine the effect of the results intervention designed in experimental and quasi-experimental model within certain fields of positive psychology in Turkey by using meta-analysis method. The National Thesis Center database and Google Scholar was used to collect the data. Experimental thesis and articles conducted in Turkey between 2000-2019 were included in the study. Relevant thesis and articles are gathered by searching with the keywords “positive psychology”, “psychological well-being”, “psychological resilience”, “mental well-being”, “hope”, “optimism”, “happiness”, “resilience”. The research focused on experimental and quasi-experimental studies, and studies with pre-test and post-test patterns were reviewed. Comprehensive Meta-Analysis program was used in the analysis of the research data. After the analysis of the data, effect sizes in various sub-dimensions were calculated. In this study, the dependent and independent variables in experimental studies carried out by the researchers in Turkey on certain topics of positive psychology and the effectiveness of the independent variables used together with the effect size calculation were examined. In order to make some calculations related to the meta-analysis of the thesis and articles included in the research, studies with the required arithmetic mean, standard deviation and sample number were examined. Studies outside the field of Psychological Counseling and Guidance, qualitative studies and studies in which related values couldn’t be calculated were not included in the research. 16 studies (2 for positive psychology, 1 for psychological well-being, 2 for psychological resilience, 4 for subjective well-being, 1 for hope, 3 for optimism, 1 for happiness, 2 for resilience) were included in meta-analysis. As a result; according to a random model this study general effect size found 0,8 (0,32-1,27), also fixed model effect size 0,6 (0,43-0,78). The data obtained has indicated that the experimental studies have effective results in acquiring certain social skills related to positive psychology and providing more psychologically happy, hopeful and positive perspectives. The small number of experimental studies reached is an important indicator of the need for different experimental studies in the field of positive psychology.